Intensitas Bermedia Sosial dan Minat Muslim Urban Berhijrah: Analisis Followers Akun Instragram @Surabayahijrah - Irawan, Rahmat Edi; Palupi, Merry Fridha Tri; Putro, Taufan Aji Santoso (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This study aims to measure the effect of the intensity of accessing Instagram account access @surabayahijrah on followers' interest to hijrah (individual muslim shifts towards a more religious way of life). This article is the result of a correlational quantitative study with the number of sample 100 followers of Instagram account @Surabayahijrah who live in Surabaya. The results have shown that r squared is 0.1186 which means that there was an influence of Instagram account access @ surabayaahijrah of 11.86% on the interest of hijrah and the rest was another factor outside of the research about 88.14%. Partial test results (t) also indicated that the t-value of 2.066> t-value of 1.667, which means that there was an influence of partial access to the account @surabayahijrah with a significance value of 0.041 which is less than the specified significance value of 0.1.